THE EFFECT OF MATERNAL AND CHILD HEALTH EDUCATION THROUGH ANTENATAL CLASS TO IMPROVE KNOWLEDGE AND ATTITUDE OF PREGNANT WOMEN - Indrayani, Triana; Riviana, Andi Julia (Yayasan Education and Social Center, 2024)
Maternal Mortality Rates (MMR) in various regions in Indonesia are diverse. Maternal and child health education is generally still carried out through individual or case-by-case consultation, which is provided when the mother has her pregnancy checked. This kind of education activity is indeed useful for handling case-by-case but has weaknesses, among others, the knowledge gained is only limited to the health problems experienced during the consultation and the education provided is not coordinated. To overcome these weaknesses, a learning method through an antenatal class (a class for pregnant women) was planned. This study used a pre-experiment with a One Group Pretest- Posttest design. The sample in this study was 35 pregnant women selected by purposive sampling. The statistical test used was the t-test. The results show that there is a significant effect of providing education to pregnant women on their knowledge and attitudes, with a calculated t-value of 5.351 on knowledge and a calculated t-value of 6.000 on attitudes. These results allow a conclusion that there is an effect of providing education to pregnant women through an antenatal class on their knowledge and attitudes. The implication of this research is that it is important to conduct scheduled classes for pregnant women to increase the knowledge of pregnant women